Self-Identity of Biracial Children: What Role Do Parents Play? - Patreese D. Ingram; Anil Kumar Chaudhary (Journal of Human Sciences and Extension, 2014)
One of the fastest growing student groups today is the biracial student population. This study is part of a larger exploratory descriptive study on biracial college students with a focus on the extent to which parents socialized their biracial children in the cultures of both parents while growing up and how these students chose to self-identify. Biracial students at a large, predominantly white, research university in the northeastern United States completed an online survey. Descriptive statistics and content analysis were used to analyze the data. The results indicated that most students had adopted a “border” identity. The majority of parents had encouraged their children to have an acceptance and pride in their biracial status. However, many students would have appreciated more exposure and knowledge of their heritages, as well as preparation for dealing with their environment as a biracial person. Students offered recommendations for parental practices to strengthen their racial identity.